Costs of ambulatory pediatric healthcare-associated infections: Central-line–associated bloodstream infection (CLABSIs), catheter-associated urinary tract infection (CAUTIs), and surgical site infections (SSIs). (3rd November 2020) - Rinke, Michael L.; Oyeku, Suzette O.; Ford, William J. H.; Heo, Moonseong; Saiman, Lisa; DeLaMora, Patricia; Rabin, Barbara; Zachariah, Philip; Rosenberg, Rebecca E.; Mirhaji, Parsa; Obaro-Best, Oghale; Drasher, Michael; et al.
Abstract: Objective: Ambulatory healthcare-associated infections (HAIs) occur frequently in children and are associated with morbidity. Less is known about ambulatory HAI costs. This study estimated additional costs associated with pediatric ambulatory central-line–associated bloodstream infections (CLABSIs), catheter-associated urinary tract infections (CAUTI), and surgical site infections (SSIs) following ambulatory surgery. Design: Retrospective case-control study. Setting: Four academic medical centers. Patients: Children aged 0–22 years seen between 2010 and 2015 and at risk for HAI as identified by electronic queries. Methods: Chart review adjudicated HAIs. Charges were obtained for patients with HAIs and matched controls 30 days before HAI, on the day of, and 30 days after HAI. Charges were converted to costs and 2015 USD. Mixed-effects linear regression was used to estimate the difference-in-differences of HAI case versus control costs in 2 models: unrecorded charge values considered missing and a sensitivity analysis with unrecorded charge considered 0. Results: Our search identified 177 patients with ambulatory CLABSIs, 53 with ambulatory CAUTIs, and 26 with SSIs following ambulatory surgery who were matched with 382, 110, and 75 controls, respectively. Additional cost associated with an ambulatory CLABSI was 5, 684 (95% confidence interval [CI], 1, 005–10, 362) and 6, 502 (95% CI, 2, 261–10, 744) in the 2 models; cost associated with a CAUTI was 6, 660 (95% CI, 1, 055, 12, 145) and 2, 661 (95% CI, −431 to 5, 753); cost associated with an SSI following ambulatory surgery at 1 institution only was 6, 370 (95% CI, 4, 022–8, 719). Conclusions: Ambulatory HAI in pediatric patients are associated with significant additional costs. Further work is needed to reduce ambulatory HAIs.